Responding to Covid-19: A Framework for Analysis - Acharya, Arabinda (Advances in Social Sciences Research Journal, 2020)
Beginning December 2019 in Wuhan in China’s Hubei province, Coronavirus (Covid -19) has overwhelmed the healthcare systems and affecting education, travels, events and the economies worldwide. Governments all over have taken or bracing themselves to take extraordinary measures to contain the threat. In some countries, the measures taken to contain the epidemic appear as putting the nation under a state of siege. Some governments are adapting rather extreme measures – complete lock-down of the cities, the provinces and even the country itself, school closures, travel ban, cancellation of flights. Questions are being asked about how much freedom we are prepared to give up, for how long and onto whose hands? The paper argues that with threats and vulnerabilities transcending national boundaries and challenging most advanced knowledge and information systems in this era of intense globalization, the need for harsh and often draconian measures can hardly be over emphasized. At the same time there could be problems and unwelcome consequences in putting too much power in the hands of the governments dealing with the threat for an indefinite period of time. In view of this, the securitization framework as put forth by the Copenhagen School could be a better tool to deal with situations of unexpected crises such as what SARS epidemic proved it to be or what Covid-19 would inevitably entail